EFIKASI TERAPI BONE MARROW MESENCHYMAL STEM CELLS (BM-MSCS) PADA PASIEN CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) - Muhammad Bariq Rifqi Pasha (2020)
Stem cells are the beginning of many cells that construct human body. The writer hopes stem cells therapy on COPD cases show reparation of the injured lung tissue due to long term exposure caused by some irritant substance. Researches about BM-MSCs therapy on COPD has shown promising result, this made the writer interested in making a research about BM-MSCs therapy on COPD patient. Research design used in this research is systematic review. The writer used PubMed as a database for the research. Result from data extraction and synthesis on six literatures with four sample group shows an outcome without without any significant adverse effect. Patients show a CRP decrease, FEV1 and FVC increase, quality of life increase, and weight increase. This outcome is the effect of anti-inflammatory property from BM-MSCs therapy. From this we can conclude that in overall BM-MSCs therapy improves the patient's condition.